2022
DOI: 10.3390/ijms232113567
|View full text |Cite
|
Sign up to set email alerts
|

WideEffHunter: An Algorithm to Predict Canonical and Non-Canonical Effectors in Fungi and Oomycetes

Abstract: Newer effectorome prediction algorithms are considering effectors that may not comply with the canonical characteristics of small, secreted, cysteine-rich proteins. The use of effector-related motifs and domains is an emerging strategy for effector identification, but its use has been limited to individual species, whether oomycete or fungal, and certain domains and motifs have only been associated with one or the other. The use of these strategies is important for the identification of novel, non-canonical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…This list of phytoplasma effectors comprises membrane-bound proteins such as IdpA, Imp, VmpA and Amp. Based on more traditional descriptions of effectors as "no TMD, secreted proteins", these proteins should be excluded, but it is known that the Amp protein interacts with the actin of insect vectors [99], and recently, Wang et al (2023) [26] showed that the expression of this protein in Nicotiana tabacum inhibits plant host defense and promotes infection by the rice orange leaf phytoplasma, validating this protein as a true effector.…”
Section: Discussionmentioning
confidence: 99%

Novel Insights into Phytoplasma Effectors

Carreón-Anguiano,
Vila-Luna,
Sáenz-Carbonell
et al. 2023
Horticulturae
Self Cite
“…This list of phytoplasma effectors comprises membrane-bound proteins such as IdpA, Imp, VmpA and Amp. Based on more traditional descriptions of effectors as "no TMD, secreted proteins", these proteins should be excluded, but it is known that the Amp protein interacts with the actin of insect vectors [99], and recently, Wang et al (2023) [26] showed that the expression of this protein in Nicotiana tabacum inhibits plant host defense and promotes infection by the rice orange leaf phytoplasma, validating this protein as a true effector.…”
Section: Discussionmentioning
confidence: 99%

Novel Insights into Phytoplasma Effectors

Carreón-Anguiano,
Vila-Luna,
Sáenz-Carbonell
et al. 2023
Horticulturae
Self Cite
“…The search for effectors based on homology was also used in the prediction of fungal and oomycete effectors by WideEffHunter and demonstrated to improve its accuracy on real tests beyond positive control [49].…”
Section: Discussionmentioning
confidence: 99%
“…Effector prediction and filtering were performed using WideEffHunter [49] and EffHunter algorithms [39]. The criteria to identify the canonical effectors were (1) protein length ≤ 400 amino acids, (2) extracellular localization, (3) the presence of a signal peptide, (4) at least 4 cysteine residues, and (5) absence of transmembrane domains.…”
Section: Prediction Of Effector Proteinsmentioning
confidence: 99%
“…Recently, the EffHunter algorithm was created and was shown to have the highest F1 score among fungal effector predictors when identifying these canonical or classical effectors [39]. A novel algorithm with the ability to identify non-canonical fungal effectors was published, Wide-EffHunter, which simultaneously possesses the ability of EffectorP 1.0 to predict effectors in non-pathogenic organisms, and the added ability of Effector P 2.0 to predict effectors in pathogenic fungi [49]. Here, 40 effector candidates (less than 10% of the effectorome) meet the classical characteristics, and this proportion coincides with WideEffHunter findings when fungal effectoromes were mined [49].…”
Section: Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation